Mitigating Chinese–Indian rhesus macaque (Macaca mulatta) hybridity at the California National Primate Research Center (CNPRC). Issue 6 (28th July 2016) - Kanthaswamy, Sree; Ng, Jillian; Broatch, Jennifer; Short, Jennifer; Roberts, Jeffrey
Abstract: The effectiveness of abating hybridity in a rhesus breeding colony was evaluated. STR data from the 2006 to 2015 newborns were analyzed. Hybridity decreased over successive years. Birth cohorts retained high genetic variability without signs of inbreeding and differentiation. Hybridity was minimized without compromising overall genetic variability.